Nanoparticles for postinfarct ventricular remodeling. (24th October 2018) - Dong, Caijuan; Ma, Aiqun; Shang, Lijun
In recent years, tremendous progress has been made in the treatment of acute myocardial infarction, but pathological ventricular remodeling often causes survivors to suffer from fatal heart failure. Currently, there is no effective therapy to attenuate ventricular remodeling. Recently, nanoparticle-based drug delivery systems are widely applied in biomedicine especially in cancer and liver fibrosis, owing to its excellent physical, chemical and biological properties. Therefore, the use of nanoparticles as delivery vehicles of small molecules, polypeptides, etc. to improve postinfarct ventricular remodeling is expected. In this review, we summarize the updated researches in this fast-growing area and suggest further works needed.